THE GROWTH AND DEVELOPMENT OF RASPBERRY CULTIVARS IN THE CONDITION OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the article during the growing season the occurence of phenological phases, the buds formation, buds opening, the beginning of flowering, full flowering and the duration and the end of flowering, the time of flowering and the condition of the plants of the raspberry cultivars grown in Uzbekistan are evaluated in points. The results of research to study the beginning of fruit ripening, full ripening, the differences and quality indicators of fruits, the average and maximum weight of the fruit, acidity and sugar content of the fruit are given. Raspberry cultivars with high yields, depending on the ripening period of the fruit, are also recommended herein